THE EFFECTIVENESS OF GROUP GUIDANCE WITH MODELING TECHNIQUES TO IMPROVE STUDENTS MOTIVATION LEARNING - Shofiah, Nuri; Suhendri, Suhendri; Lestari, Farikha Wahyu (Bisma The Journal of Counseling, 2020)
This research is motivated because of low learning motivation shown by sleepy behavior during class hours, often forgetting assignments given by the teacher, cheating on friends' work, less attractive to him in doing assignments, difficulty understanding lessons, learning if there are exams or tests, discouraging each face difficulties. This research was conducted quantitatively in a quasi-experimental design with the form of a pretest-posttest control group design. The population in this study were all students of class XI Kesatrian 2 Semarang High School. Samples taken in this study were 34 students of class XI IPS 3 which were divided into two groups, namely the experimental group of 17 students and the control group of 17 students. With the determination of research subjects using simple random sampling techniques. The data of this study were obtained through a psychological scale of learning motivation. Then the modeling guidance services provided by the modeling technique are on target and on the right material. This is because students after getting a modeling technique group guidance services can apply effective study habits, able to increase enthusiasm in achieving learning goals. Suggestions for supervising teachers are expected to help the supervising teacher to find out student competencies in enhancing learning motivation.